Findings by an International Collaboration on SJS/TEN With Severe Ocular Complications - Ueta, Mayumi (Frontiers in Medicine, 2021)
Stevens-Johnson Syndrome (SJS) is an acute inflammatory vesiculobullous reaction of the skin and mucosa, e.g. the ocular surface, oral cavity, and genitals. In patients with extensive skin detachment and a poor prognosis, the condition is called toxic epidermal necrolysis (TEN). Not all, but some patients with SJS/TEN manifest severe ocular lesions. Approximately 50% of SJS/TEN patients diagnosed by dermatologists and in burn units suffer from severe ocular complications (SOC) such as severe conjunctivitis with pseudomembrane and ocular surface epithelial defects in the acute stage. In the chronic stage, this results in sequelae such as severe dry eye and visual disturbance. Before 2005, our group of Japanese scientists started focusing on ophthalmic SJS/TEN with SOC. We found that cold medicines were the main causative drugs of SJS/TEN with SOC and that in Japanese patients, HLA-A*02:06 and HLA-B*44:03 were significantly associated with cold medicine-related SJS/TEN with SOC (CM-SJS/TEN with SOC). We expanded our studies and joined scientists from Korea, Brazil, India, Taiwan, Thailand, and the United Kingdom in an international collaboration to detect the genetic predisposition for SJS/TEN with SOC. This collaboration suggested that in Japanese patients, cold medicines, including NSAIDs, were the main causative drugs, and that HLA-A*02:06 was implicated in Japanese and Korean patients and HLA-B*44:03 in Japanese-, Indian-, and Caucasian Brazilian patients. Our joint findings reveal that there are ethnic differences in the HLA types associated with SJS/TEN with SOC.